Peningkatan Pengetahuan Keislaman dan Kesadaran Beragama pada Masyarakat Kelurahan Mataallo Kecamatan Bajeng Kabupaten Gowa - Azwar Azwar; Syaibani Mujiono; Muh. Usman (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
The purpose of the Real Work Lecture (KKN) V of STIBA Makassar students is to increase the Islamic knowledge and religious awareness in the community of Mataallo Village, Bajeng District, Gowa Regency. This KKN is a form of community service as a pillar of the Tridarma Perguruan Tinggi. The method of implementing this activity is to map the problems and needs first using the SOAR analysis instrument. After analyzing the problems and needs, work programs are prepared according to the needs of the community. The work programs that have been successfully implemented are Pelatihan Penyelenggaraan Jenazah, Pesantren Ramadan, and Festival Anak Saleh. The results of the activities are the enthusiasm and support of the community for each activity, especially the government and the students and youth. The community feels great benefits after participating in various KKN programs, including the increase in knowledge, insight and religious practices, especially related to the organization of corpses, taharah, prayer and fasting, as well as reading and writing the al-Qur’an. The sustainability of this program is in the form of further coaching for participants, especially training on the handling of abnormal corpses, such as corpses with certain diseases, accident victims, victims of natural disasters, and others, which require special treatment and are different from corpses in general; need to continue to accompany students of SMP-SMA Aksara especially in the religious field by adding several teachers who focus on the religious field and coordinating students with religious organizations at the junior and senior high school levels; as well as the need for efforts from their respective Kindergarten/TPA caregivers to continue fostering and deepening the interests and talents of the students.